UTC(OP) based on LNE-SYRTE atomic fountain primary frequency standards. (20th May 2016) - Rovera, G D; Bize, S; Chupin, B; Guéna, J; Laurent, Ph; Rosenbusch, P; Uhrich, P; Abgrall, M
Abstract: UTC(OP), the French national realization of the international coordinated universal time, was redesigned and rebuilt. The first step was the implementation in October 2012 of a new algorithm based on a H-maser and on atomic fountain data. Thanks to the new implementation, the stability of UTC(OP) was dramatically improved and UTC(OP) competes with the best time scales available today. Then the hardware generation and distribution of the UTC(OP) physical signals were replaced. Part of the new hardware is composed of commercial devices, but the key elements were specifically developed. One of them is a special switch that allows the UTC(OP) signals to be derived from one of two time scales, based on two different H-masers, which are generated simultaneously. This insures the continuity of the UTC(OP) signal even when a change of the reference H-maser is required. With the new hardware implementation, UTC(OP) is made available through three coherent signals: 100 MHz, 10 MHz and 1 PPS. For more than 3 years, UTC(OP) remained well below 10 ns close to UTC, with a difference even less than 5 ns if we except a short period around MJD 56650.